Two new species of the Neotropical spittlebug genus Monecphora Amyot & Serville (Hemiptera: Cercopidae) with key and notes of species of the genus - Carvalho, Gervásio Silva; Sakakibara, Albino Morimasa; Webb, Michael D. (Zootaxa, 2016)
Two new species of the Neotropical spittlebug genus Monecphora Amyot & Serville are described: Monecphora machadoi sp. nov. (Holotype male deposited in NMW: Brazil, “Natterer”) and Monecphora broomfieldi sp. nov. (Holotype male deposited in BMNH: Costa Rica, Turrialba, 3–8.VII.1981, W.R. Dolling leg.) and a key and notes to species of the genus are provided. Lectotypes are designated for Tomaspis fryi Distant, Monecphora nigritarsis Stål, and Monecphora semilutea Stål. In addition, two corrections are made to the Cercopid Spittlebugs of the New World (Carvalho & Webb 2005) with respect to figures 70–73 and 193–194 (see Corrigenda).